New dimensions for hospital services and early detection of disease: a Review from the Lancet Commission into liver disease in the UK. Issue 10286 (8th May 2021) - Williams, Roger; Alessi, Charles; Alexander, Graeme; Allison, Michael; Aspinall, Richard; Batterham, Rachel L; Bhala, Neeraj; Day, Natalie; Dhawan, Anil; Drummond, Colin; Ferguson, James; Foster, Graham; et al.
Summary: This Review, in addressing the unacceptably high mortality of patients with liver disease admitted to acute hospitals, reinforces the need for integrated clinical services. The masterplan described is based on regional, geographically sited liver centres, each linked to four to six surrounding district general hospitals—a pattern of care similar to that successfully introduced for stroke services. The plan includes the establishment of a lead and deputy lead clinician in each acute hospital, preferably a hepatologist or gastroenterologist with a special interest in liver disease, who will have prime responsibility for organising the care of admitted patients with liver disease on a 24/7 basis. Essential for the plan is greater access to intensive care units and high-dependency units, in line with the reconfiguration of emergency care due to the COVID-19 pandemic. This Review strongly recommends full implementation of alcohol care teams in hospitals and improved working links with acute medical services. We also endorse recommendations from paediatric liver services to improve overall survival figures by diagnosing biliary atresia earlier based on stool colour charts and better caring for patients with impaired cognitive ability and developmental mental health problems. Pilot studies of earlier diagnosis have shown encouraging progress, with 5–6% of previously undiagnosed cases of severe fibrosis or cirrhosis identified through use of a portable FibroScan in primary care. Similar approaches to the detection of early asymptomatic disease are described in accounts from the devolved nations, and the potential of digital technology in improving the value of clinical consultation and screening programmes in primary care is highlighted. The striking contribution of comorbidities, particularly obesity and diabetes (with excess alcohol consumption known to be a major factor in obesity), to mortality in COVID-19 reinforces the need for fiscal and other long delayed regulatory measures to reduce the prevalence of obesity. These measures include the food sugar levy and the introduction of the minimum unit price policy to reduce alcohol consumption. Improving public health, this Review emphasises, will not only mitigate the severity of further waves of COVID-19, but is crucial to reducing the unacceptable burden from liver disease in the UK.